The problem of overskilling in Australia and Britain - Kostas Mavromaras; Seamus McGuinness; Nigel C. O'Leary; Peter J. Sloane; Yi King Fok (Institute for the Study of Labor (IZA), 2007)
This paper examines the parallel trends in education and labour market developments in Australia and Britain. It uses unique information in the WERS and HILDA surveys on reported overskilling in the workplace. To a degree, the overskilling information overcomes the problem of unobserved ability differences and focuses on the actual job-employee mismatch more than the conventional overeducation variables can. The paper finds that the prevalence of overskilling decreases with education at least for Australia, but the wage penalty associated with overskilling increases with education. Although the general patterns of overskilling (prevalence and penalties) are fairly similar between Australia and Britain, the problem appears to be greater in Britain.
Keywords: 330; Overskilling; overeducation; Australia; Britain; Überqualifikation; Lohn; Bildungsertrag; Schätzung; Australien; Großbritannien